Responding to problem behavior in schools the check-in, check-out intervention - Hawken, Leanne S.; Bundock, Kaitlin; Crone, Deanne A.; Horner, Robert H. (The Guilford practical intervention in the schools series, 2021)
"Now revised and expanded with the latest research and adaptations for additional target behaviors, this is the gold-standard guide to Check-In, Check-Out (CICO), the most widely implemented Tier 2 behavior intervention. CICO is designed for the approximately 10-15% of students who fail to meet schoolwide behavioral expectations but who do not require intensive, individualized supports. In a large-size format with lay-flat binding for easy photocopying, the book includes step-by-step procedures and reproducible tools for planning and implementation. At the companion website, purchasers can download and print the reproducible tools and can access online-only training materials, sample daily progress reports, and an Excel database for managing daily data. (Second edition subtitle: The Behavior Education Program.) Key Words/Subject Areas: CICO, Tier 2, II, behavior education program, behavior support teams, positive behavior interventions and supports, PBIS, daily progress reports, implementation guide, behavioral problems, training workshops, attendance, academic engagement, prevention, elementary students, secondary, children, adolescents, school psychology, school psychologists Audience: School psychologists, school counselors, school social workers, and administrators working with children ages 4-17 (grades PreK-12); PBIS coaches and team leaders; special educators"--